Di Antara Tahu dan Patuh: Eksplorasi Pemahaman Perpajakan dalam Perspektif Wajib Pajak - Nisrina, Ulfah Laila (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This study aims to explore taxpayers’ understanding of taxation and its relationship with tax compliance from the taxpayers’ perspective. While tax policy commonly assumes that increased understanding leads to higher compliance, this study challenges the linearity of such an assumption by positioning the relationship between knowing and complying as a complex social phenomenon. Employing a qualitative approach within an interpretive paradigm, this research examines taxpayers’ experiences, interpretations, and considerations in fulfilling their tax obligations. Data were collected through in-depth interviews with individual taxpayers selected purposively and analyzed using thematic analysis. The findings reveal that taxpayers’ understanding of taxation is largely procedural rather than conceptual, while compliance is often driven by external factors such as sanctions and administrative pressure. Moreover, higher levels of understanding do not necessarily result in greater compliance; instead, they may foster critical attitudes toward the perceived fairness and transparency of the tax system. Perceptions of justice, trust in the state, and social environment significantly shape how taxpayers interpret and respond to their tax obligations. This study concludes that tax compliance is a socially embedded phenomenon influenced by the interaction of knowledge, experience, and social context. Therefore, efforts to enhance tax compliance should move beyond technical education toward more human-centered and dialogical approaches.